Corporate digital transformation and carbon mitigation: Chain effects and evidence from China - Deng, Xiujie; Huang, Yuhan; Fu, Wanting; Liang, Xuedong (International journal of production economics, 2025)
This study utilizes a sample of 29,118 observations of Chinese firms from 2011 to 2022, combined with the endogenous growth model, to systematically analyze the mechanisms by which digital transformation affects carbon emissions. The empirical results demonstrate that digital transformation contributes to the reduction of carbon emissions. After a series of endogeneity treatments and alternative measures, the findings remain statistically significant and consistent. In terms of mechanism analysis, the emission-reducing effect of digital transformation is not limited to the singular impacts of technological progress or energy efficiency (or energy structure). It can also further reduce carbon emission intensity through two chain mediation pathways: “technological progress → energy efficiency” and “technological progress → energy structure.” Industry-level analysis shows that digital transformation mainly operates through internal firm effects and entry effects, thereby promoting inter-industry technological spillovers and enhancing the efficiency of resource allocation. Furthermore, the carbon reduction effect of digitalization exhibits significant heterogeneity across industries and regions, with the most pronounced effects observed in low-emission industries, strategic emerging sectors, and the eastern region of China. This study contributes not only to the theoretical discourse on data-driven digital transformation and operational management, but also provides practical insights for environmental governance across different industries and sectors.